MULTI-POLARIZATION FOR ANALYSIS OF GEOLOGICAL STRUCTURES AS FORMATION OF HYDROCARBON TRAPS CONTROLLER IN EAST JAVA BASIN - Indah Crystiana; Hartono Hartono; Retnadi Heru Jatmiko; Taufan Junaedi (Testing Center for Oil and Gas LEMIGAS, 2018)
The decline in oil reserves and the increasing demand for oil and gas energy led to the search for new reserves. The geological structure pattern used to know the pattern of distribution and formation of hydrocarbons traps in the East Java Basin is one of the important information that can be extracted through remote sensing data of multi-polarization system. The multi-polarization system of this study merged the Alos Palsar imagery with HH and HV polarization, and Sentinel Image polarized VV and VH. Processing both image data through calibration, multilook, speckle fi ltering, geometric correction and mosaic. Filtered imagery is composite and sharpening. The fi ltering technique use Lee 5x5 kernel fi lter and then continue with 5x5 median fi lter. The results of multi-polarization system image interpretation can be identifi ed by fold, thrust faults, normal faults, strike-slip faults, bedding, and closure structure. In the formation research area the structure lasted two periods, with the main emphasis N-S in the order of 1 and the main direction of the SW-NE direction in the order-2. The hydrocarbon traps and exploration targets can be distinguished in three zones (Zone A, Zone B, and Zone C). Closure in Zone A includes closures 3, 4, 5, 7, 8, 9, 10, 11, 22, 23, 24, 25, 26, 27, 28, 29, 30. Closure in Zone B includes closures 1, 2, 6, 12, 13, 14, 15, 16, 17, 31, 32. Closure on Zone C includes closure18, 19, 20, 21.